1044 Adequate Sleep is Associated with Improved Diabetes Knowledge and HbA1c. (27th May 2020) - Pandey, A; Cooper, L; Zrebiec, J; Spadola, C; Bennett, R L; Rosenthal, M M; Littlewood, K
Abstract: Introduction: Although 55 % of the people with T2DM have low quality of sleep that may affect their physical and emotional wellbeing, and present challenges to the management of their condition, many Diabetes Self-Management Education Programs (DSME) that aim to improve knowledge of T2DM, don't include information on healthy sleep. This study will examine the relationship between adequate sleep on improved T2DM knowledge and diabetes maintenance (HbA1c). Methods: The Sleep Integrated with Diabetes Education (SLIDE) Trial tests whether including four brief healthy sleep hygiene sessions within an existing traditional Diabetes Self-Management Education Program improves healthy sleep, motivation for change, and biopsychosocial outcomes for 50 patients with DM who are under and uninsured. This study uses descriptive and ANOVAs to examine the relationship between adequate sleep and change in diabetes knowledge (Diabetes Knowledge Test) using self-report. EMR was used to link HbA1c and other biological measures. Results: Fifty patients with T2DM (mean HbA1c = 8.79 ± 2.42) participating in a DSME Program at a southern urban community nonprofit hospital were randomly assigned to DSME classes or DSME classes + four 15-minute presentations (video and powerpoint) highlighting healthy sleep hygiene practices. The majority of these patients were obese (mean BMI=38.56±8.20). Only 11% reported normal sleep, with 41% reporting short sleep (<6 hours) and 7% long sleep (>8 hours). Patients who reported adequate sleep were more likely to improve diabetes knowledge (81% score vs. 68% score, p<.001) and HbA1c (1.1 vs. -.03, p<.001). Conclusion: There is a relationship between adequate sleep and improving diabetes knowledge and maintenance for patients with T2DM. Future research could further explore this relationship and determine barriers and facilitators to adequate sleep and what role adequate sleep plays in improving T2DM knowledge and maintenance. Support: Bon Sequor Foundation